(untitled) (Medical Forum Monthly, 2024)
Background: The prostate gland is found at the base of the bladder, surrounding the urethra. A rising interest has been noted in the diseases of the prostrate in the last decade or so. This is attributed to the fact that a high incidence of the prostatic carcinoma has been noted in different geographical locations and multi ethnic groups. Carcinoma of the prostate is the most common form of cancer in males in the United States, second only to lung cancer. Study Design: retrospective study Place and Duration of Study: This study was carried out at Department of pathology, Dow Medical College, Karachi between January 2003-2012. Materials and Methods: A retrospective study of 317 prostatic biopsies was conducted, based on the histopathological reports, with the purpose of identifying patients with prostatic lesions. Records of all specimens of prostatic tissue received for histopathology from the Civil hospital Karachi were used in this study. The data obtained were subjected to descriptive statistical analysis using SPSS version 16.0. Results: The total number of patients included in this study was 317. The mean age of the patients was 64.9±8.12 with an age range of 48-100. 7.9% (n=25) patients had prostatic adenocarcinoma whereas 91.8% of patients showed benign nodular hyperplasia. Conclusion: Overall the incidence of prostatic cancers is more in the western countries as compared to the east. This can be attributed to the fact that the west has screening programs that leads to early detection. However screening programs should also be introduced and made available to general public and in males over the age of 50, PSA level detection should be made compulsory.